High Neutrophil-to-Albumin Ratio Predicts Postoperative Pneumonia in Aneurysmal Subarachnoid Hemorrhage - Zhang, Xin; Zhang, Sheng; Wang, Congkai; Liu, Ran; Li, Aimin (Frontiers in Neurology, 2022)
Background & Aim: Although there are a variety of risk factors for postoperative pneumonia (POP) in patients with aneurysmal subarachnoid hemorrhage (aSAH), objective and easily accessible biomarkers are still lacking. In this study, we evaluated the relationship between the neutrophil-to-albumin ratio (NAR) and POP in patients with aSAH. Methods: We retrospectively assessed 395 consecutive patients who underwent clipping or coiling of the aneurysm, analyzed the existing population data and baseline variables of these patients. Patients were divided into POP and did not occur. The recipient operation feature (ROC) curve and logic regression analysis is used to identify independent predictors. Results: Among the 395 patients, POP occurred in 78(19.7%) in this cohort. Patients with POP had significantly higher NAR than those without (0.31[0.25-0.39] vs 0.23[0.18-0.28]; P<0.001). Multivariate logistic regression analysis showed that NAR (odds ratio=1.907; 95% confidence interval, 1.232-2.953; P=0.004) on admission was independently associated with POP after adjusting for confounders. Besides, the predictive performances of NAR for POP was significantly (AUC [95% CI] 0.775 [0.717-0.832]; P < 0.001). Conclusions: NAR elevation at admission might be informative for predicting POP in patients with aSAH.